Developing a Mobile Game Using Scientific Approach to Support Mathematics Learning - Rhomiy Handican; Wahyu Setyaningrum (Edumatika : Jurnal Riset Pendidikan Matematika, 2021)
The widespread use of smartphones to play games and the lack of use as a medium for learning mathematics is the reason for the need for the development of smartphone-based edutainment learning media. The purpose of this research is to design and develop interactive edutainment learning applications of mobile mathematics games to help junior high school students to learn line and angles material. This mobile game-based application incorporates graphic design, background music, and animation, and a major structural element in game development to attract students. This research belongs to the type of Research and Development (R&D) and the model used is the ADDIE model that is carried out in a systematic stage. The results of the study show that the developed game meets the valid aspects, where the level of expert approval of the design functionality has an average value of 4,49 out of 5, meanwhile, the assessment of the material has an average score of 4,17 out of 5 and the user states that the game meets the practical aspect with an average score of  3,75 out of 5. It is hoped that this game-based learning application called "CORNER" for mobile devices can act as an additional tool for improving students' conceptual understanding and interest to learn through the scientific approach used.